2011
DOI: 10.1167/iovs.11-8169
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Inner Retinal Dysfunction in Mice Lacking Sigma Receptor 1 (σR1)

Abstract: These data suggest that lack of σR1 leads to development of late-onset retinal dysfunction with similarities to optic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(113 citation statements)
references
References 51 publications
7
106
0
Order By: Relevance
“…We do not know which retinal cell type-the degenerating neuron or supportive cells such as Müller cells-is targeted using (+)-PTZ. Earlier in vitro studies demonstrated attenuation of oxidative stress-induced death of isolated RGCs when pretreated with (+)-PTZ, suggesting that the ligand has a direct protective effect on neurons (29). However, (+)-PTZ treatment also can attenuate cytokine release (16) and oxidative stress (31) in isolated Müller cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We do not know which retinal cell type-the degenerating neuron or supportive cells such as Müller cells-is targeted using (+)-PTZ. Earlier in vitro studies demonstrated attenuation of oxidative stress-induced death of isolated RGCs when pretreated with (+)-PTZ, suggesting that the ligand has a direct protective effect on neurons (29). However, (+)-PTZ treatment also can attenuate cytokine release (16) and oxidative stress (31) in isolated Müller cells.…”
Section: Discussionmentioning
confidence: 97%
“…Sig1R is bound to ceramide-enriched microdomains in complex with the binding protein/glucose regulated protein 78 (GRP78/BiP) protein and functions as an ER chaperone involved in Ca 2+ mobilization (12). It regulates neuronal nitric oxide synthase, prevents apoptotic neuronal cell death (13,14), and modulates the activity of pleiotropic transcription factors including NFκB (15,16) (27) that is worsened by stress such as optic nerve crush or diabetes (28)(29)(30). Retinal Müller glial cells isolated from Sig1R…”
mentioning
confidence: 99%
“…ROS has been reported to be involved in signaling RGC death by acting as a second messenger and/or modulating protein function in conditions such as glaucoma [121][122][123] and ischemic injuries of the retina [107,124]. Hypoxia and oxidative stress are also involved in the development of diabetic retinopathy [125] resulting in RGC death [126]. Increased lipid peroxidation (LPO) and depletion of antioxidants such as GSH in response to hypoxia/reoxygenation have been reported by us to cause damage to RGCs [43].…”
Section: Hypoxia and Oxidative Stressmentioning
confidence: 99%
“…The sources and concentrations of primary and secondary antibodies are provided in the Table. Retinal cryosections were prepared from cbs þ/þ , cbs þ/À , and cbs À/À mice per our previously described method. 21 Sections were fixed with 4% paraformaldehyde, washed with PBS-Triton X-100, incubated with Power Block (BioGenex), and then incubated with primary antibody for either 3 hours at 378C or overnight at 48C; the sections were washed thrice with PBSTriton X-100 followed by incubation with secondary antibody for 1 hour at 378C. Sections were washed with PBS-Triton X-100 and coverslipped with Fluoroshield with 4 0 6-diamidino-2-phenylindole (DAPI) (Sigma Chemical Corp., St. Louis, MO) to label nuclei.…”
Section: Immunofluorescence Of Vascular Markers In Retinal Cryosectionsmentioning
confidence: 99%